Towards sustainable biofuel production: Design of a new biocatalyst to biodiesel synthesis from waste oil and commercial ethanol - Ferrero, Gabriel Orlando (2016)
The sustainable technologies to produce alternative energies as biofuel with focus on the harnessing of renewable sources and waste biomass is gradually gaining ground. Although the biodiesel is a very attractive biofuel its production from vegetable oils competes with the feed generation with the consequent socio-economic costs involved. Therefore, the reuse of waste oils appears as an alternative highly promising. However the high content of free fatty acid and water in this raw material difficult its use in the conventional processes employed in the actuality. In this work, we successfully develop hybrid catalysts based in Pseudomonas fluorescens lipase immobilized over Ca and Na modified mesoporous SBA-15 supports. The physic-chemical properties of the supports were determined by Small-angle X-ray Scattering (SAXS), Transmission Electron Microscopy (TEM), Scanning Electron Microscope (SEM), Infrared Spectroscopy (IR), Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP) and N2 adsorption measurements. These hybrid catalysts were capable to process waste oils, and even, commercial ethanol (96%) obtained from a fermentative process An optimum activity, with around 90% of FAEE yield, was achieved with lipase immobilized on Ca modified SBA-15 using 4% of water respect to oil, 1:4 oil/ethanol ratio, 400 mg/g of enzyme immobilized, at 37 °C and 180 oscillations/min. This catalyst could contribute to development of a more environmentally and economically viable process to biodiesel production.